Agile-Based Payroll Application Development to Improve Efficiency and Accuracy of Payroll in Cargo Companies - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research aims to address the efficiency and accuracy of the payroll process in a cargo company through the development of an Agile-based application. The problems identified include payroll processes that are still manual, prone to errors and need more flexibility in adapting the system to rapid changes in the logistics industry. The research methods used are user needs analysis, Agile-based planning, application development with design and prototyping, and functional, performance, and security testing. The expected result is implementing a payroll application that is efficient, accurate, and responsive to changes to increase productivity, reduce payroll errors, and increase employee satisfaction in cargo companies. The contribution of this research is to provide practical solutions for cargo companies in optimizing payroll management by utilizing Agile-based technology and providing a framework that can be used as a foundation for developing similar applications in the logistics industry.